(I1 – I2) R2 = 0 or VB = I1 - UCSD Department of Physics

```This handout covers the two-loop circuit that we discussed in class. It is important to
understand this general case, as two-loop circuits form the basis of many biological problems –
e.g., neuronal dendrites that are at a different potential than the soma, coupled biochemical
reactions, etc. – and even practical issues like to how to run multiple electrophoresis gels when
you are down to one power supply!
Loop 1
-VB + I1R1 + (I1 – I2) R2 = 0
or
VB = I1 (R1 + R2) – I2 R2 .
Loop 2
(I2 – I1) R2 + I2 R3 = 0
or
R2
I 2 = I1
.
R2 + R 3
Thus
VB
= I1 (R1 + R2) – I1
= I1 (R1 + R2)
R2
R2
R2 + R 3
R2 + R 3
R2
– I1
R2
R2 + R 3
R2 + R 3
R 1R 2 + R 1R 3 + R22 + R 2R 3 − R22
= I1
R2 + R 3
= I1
R 1R 2 + R 1R 3 + R 2R 3
.
R2 + R 3
Thus
I1
= VB
R2 + R 3
R 1R 2 + R 1R 3 + R 2R 3
I2
= VB
R2 + R 3
R2
R 1R 2 + R 1R 3 + R 2R 3 R 2 + R 3
= VB
R2
R 1R 2 + R 1R 3 + R 2R 3
I1-I2 = VB
= VB
and
I1-I2 = VB
R2 + R 3
R2
- VB
R 1R 2 + R 1R 3 + R 2R 3
R 1R 2 + R 1R 3 + R 2R 3
R3
.
R 1R 2 + R 1R 3 + R 2R 3
R2 + R 3
R2
- VB
R 1R 2 + R 1R 3 + R 2R 3
R 1R 2 + R 1R 3 + R 2R 3
Current Division
Current through R1 is I1, which is the total current supplied by the battery.
Current through resistor R2 is (I1 – I2) = I1
Current through resistor R3 is I2 = I1
R3
R 2 + R 3
R2
R 2 + R 3
For the in-class demonstration, we let R ≡ R1 = R2 = R3,
I1 =
VB 2
2
, e.g., voltage drop across R1 is I1R1 = VB .
R 3
3
I2 =
VB 1
1
, e.g., voltage drop across R3 is I2R3 = VB; same as the drop across R2.
R 3
3
How well do these match with the measured values?
```